More Than Personal Communication: Templates For Citing Indigenous Elders and Knowledge Keepers - MacLeod, Lorisia (KULA)

(untitled) (University of Victoria Libraries, 2021)
In this project report, I introduce the citation templates for Indigenous Elders and Knowledge Keepers that I created in partnership with the staff of the NorQuest Indigenous Student Centre. These citation templates have been adopted/linked to by twenty-five institutions across Canada and the United States. They represent an attempt to formalize something that Indigenous scholars have been doing for decades: fighting to find a better way to acknowledge our voices and knowledges within academia. I outline how the project was developed, highlighting the importance of stable, respectful relationships, before delving into some of the literature and personal experiences that provided the reasoning for why more culturally responsive citation is needed. Part of the background is acknowledging my own experiences as an Indigenous scholar, but I also draw on literature from both Indigenous and non-Indigenous scholars to illustrate the interdisciplinary need for these templates. I provide in-depth explanations of each element in the new citation templates to explain the reasoning behind and/or importance of each element. For example, I outline why including the individual’s nation/community is important for breaking down the pan-Indigenous stereotype and helping scholars to recognize the variation of knowledge across the hundreds of unique Indigenous communities. While the main focus of this paper will be these specific citation templates, I hope that it will also empower, inspire, and provide a case study of how academia can make small changes to improve the respectful recognition of Indigenous knowledges and voices. Given the recent focus in educational institutions on being more inclusive of Indigenous ways of knowing, I think it is only right that we also look at reconsidering how we treat things like Indigenous oral knowledge in academia and whether there are systems in place that implicitly prioritize written knowledge over oral knowledge in a form of ongoing colonialism.